2020
DOI: 10.3390/nu12061889
|View full text |Cite
|
Sign up to set email alerts
|

Rice Bran Phenolic Extracts Modulate Insulin Secretion and Gene Expression Associated with β-Cell Function

Abstract: Oxidative stress is known to modulate insulin secretion and initiate gene alterations resulting in impairment of β-cell function and type 2 diabetes mellitus (T2DM). Rice bran (RB) phenolic extracts contain bioactive properties that may target metabolic pathways associated with the pathogenesis of T2DM. This study aimed to examine the effect of stabilized RB phenolic extracts on the expression of genes associated with β-cell function such as glucose transporter 2 (Glut2), pancreatic and duodenal homeobox 1 (Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…Concurrently, Tantipaiboonwong et al (2017) demonstrated that red rice extract, which contains phenolic compounds, flavonoids, proanthocyanidins, and other bioactive compounds, effectively lowered hyperglycemia in streptozotocin-induced diabetic rats. Recent in vitro studies also documented that rice bran and colored rice phenolic extracts enhanced β-cell function by modulating insulin expression and secretion ( Kang et al, 2020 ; Saji et al, 2020 ). Our preliminary phytochemical screening of RRBE confirmed the findings of these studies and demonstrated the presence of phenolics and flavonoids (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrently, Tantipaiboonwong et al (2017) demonstrated that red rice extract, which contains phenolic compounds, flavonoids, proanthocyanidins, and other bioactive compounds, effectively lowered hyperglycemia in streptozotocin-induced diabetic rats. Recent in vitro studies also documented that rice bran and colored rice phenolic extracts enhanced β-cell function by modulating insulin expression and secretion ( Kang et al, 2020 ; Saji et al, 2020 ). Our preliminary phytochemical screening of RRBE confirmed the findings of these studies and demonstrated the presence of phenolics and flavonoids (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Also, another study reported that procyanidins increased the amount of GLUT4 in the plasma membrane of both adipocytes ( Pinent et al, 2004 ) and muscles ( Yamashita et al, 2016 ) and that proanthocyanidins improved insulin sensitivity in the livers of rats fed with a high-fat fructose diet by activating the insulin-signaling pathway ( Yogalakshmi et al, 2014 ). Moreover, treatment of β-cells with rice bran and red rice phenolic extracts increased the expression of GLUT2, resulting in increased β-cell function ( Kang et al, 2020 ; Saji et al, 2020 ). Other rice bran compounds, such as ferulic acid and γ-oryzanol, have also been observed to demonstrate anti-diabetic activities, and the presence of these compounds in the RRBE cannot be ruled out ( Mattei et al 2021 ; Pereira et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…These phenolic components play an important role in modulating the expression of genes involved in pancreatic β-cell dysfunction and insulin secretion through several mechanisms, namely:1) synergistic action between polyphenols and phenolic acids in targeting signaling molecules, such as transcription factors; 2) reducing radical damage related to pancreatic β-cell dysfunction through antioxidant activity; and 3) triggering effectors and factors responsible for the continuity of insulin secretion (Saji et al, 2020).…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…In this Special Issue on "Dietary Polyphenols and Human Health", a series of 10 papers are presented, including three literature reviews [6][7][8] and seven original research papers [9][10][11][12][13][14][15]. The described research contributes to filling some of the gaps in our knowledge about the beneficial effects of dietary polyphenols on chronic health conditions, notably cardiovascular disease, type 2 diabetes, neurological impairment, and also certain risk factors.…”
mentioning
confidence: 99%
“…The final two publications shed light on the mechanism of action of polyphenols. Saji et al explore how a rice bran phenolic extract could target metabolic pathways associated with Type 2 diabetes mellitus, concluding that it modulated the expression of genes involved in β-cell dysfunction and insulin secretion through different mechanisms [14]. Focusing on the pathogenesis of cardiovascular diseases, Nignpense et al performed a clinical trial with healthy volunteers to evaluate the effect of ingesting a sorghum extract.…”
mentioning
confidence: 99%